Adaptive parenting for alleviating young children's shyness: A randomized controlled trial of an early intervention program. Issue 6 (28th February 2017) - Luke, Felix; Chan, Charles C.; Au, Alma; Lai, Simon M.K.
Abstract: A randomized controlled trial was conducted to test the efficacy of the Cool Little Kids program implemented for parents of temperamentally inhibited Hong Kong Chinese preschool‐aged children. This early intervention program was designed to help inhibited children alleviate shy and anxious behaviors in social situations by training parents on adaptive parenting skills. Parents of 57 inhibited children (mean age = 3.91, 35 boys) were randomly assigned to an intervention group and a waitlist control group. Children were assessed by teachers on Chinese shyness, social initiative, and internalizing problems before and after the intervention to evaluate the program effects. As hypothesized, relative to the control group, children from the intervention group reduced significantly with a large effect size detected (Cohen's f = .40) in anxious shyness but not regulated shyness. However, the same children did not significantly improve on social initiative with peers nor decrease in internalizing problems. These results were discussed with some plausible explanations. The randomized controlled trial supported wider dissemination of this preventive intervention for alleviating anxious shyness in early childhood. The positive parental receptivity also demonstrated the feasibility of a larger‐scale implementation. A future community‐wide program rollout for Chinese families in Hong Kong is warranted. Highlights: This paper investigates if parenting intervention can help reduce anxious shyness among Hong Kong Chinese children. A randomized controlled trial evidenced the efficacy of the Cool Little Kids program in alleviating Chinese children's shyness. Wider dissemination of this early intervention program in the Hong Kong Chinese community is supported by this paper.